Maternal smoking during pregnancy and rapid weight gain from birth to early infancy - Mine, Tomosa (J Epidemiol, 2016)
BACKGROUND: Although several studies have focused on the association between maternal smoking during pregnancy and rapid weight gain (RWG) during infancy, the dose-response relationship has not yet been confirmed, and very few studies have included Asian populations. Using a record-linkage method, we examined the association between maternal smoking during pregnancy and RWG in infants at around 4 months of age to clarify the dose-response relationship. METHODS: Two databases were used: maternal check-ups during pregnancy and early infancy check-ups (between April 1, 2013 and March 31, 2014 in Okinawa, Japan) were linked via IDs and provided to us after unlinkable anonymizing. For 10,433 subjects (5229 boys and 5204 girls), we calculated the change in infants' weight z-score by subtracting the z-score of their birth weight from their weight at early infancy check-ups. Smoking exposure was categorized into five groups. We used Poisson regression to examine the association of maternal smoking during pregnancy with RWG in early infancy. RESULTS: Overall, 1524 (14.6%) were ex-smoker and 511 (4.9%) were current smoker. Compared with the reference category of non-smokers, the adjusted risk ratio of RWG was 1.18 (95% confidence interval [CI], 1.06–1.32) for ex-smokers, 1.18 (95% CI, 0.93–1.50) for those who smoked 1–5 cigarettes per day, 1.57 (95% CI, 1.24–2.00) for those who smoked 6–10 cigarettes per day, and 2.13 (95% CI, 1.51–3.01) for those who smoked ≥11 cigarettes per day. There was a clear dose-response relationship. CONCLUSION: Our study suggests that maternal smoking during pregnancy is associated in a dose-dependent manner with increased risk of RWG in early infancy.